Water-sediment distribution and behaviour of Polonium (²¹⁰Po) in a shallow coastal area with high concentration of dissolved organic matters in water, North Vietnam - Tran , Thi Van; Nguyen , Duc Tam; Dang , Duc Nhan; Nguyen , Quang Long; Duong , Van Thang; Bui , Duy Cam (Nuclear Science and Technology, 2016)
The behaviour and water-sediment distribution of particle-reactive Polonium-210 in the marine environment with high concentration of total suspended particulates (TSP) and dissolved organic matters (DOC) along the coast of the Tonkin Gulf (North Vietnam) were investigated. It was revealed that the water-sediment distribution coefficient, Kd(s), of 210Po varied from 2.39x103 to 1.9x104 (L kg-1) and from 7x103to 2.5x105 (L kg-1), respectively, in the rainy and dry season. This implies that in the aquatic environment 210Po tends to be of high affinity to suspended particulates. The 210Po Kd(s) was positively correlated with salinity in both rainy and dry seasons. With DOC the Kd(s) was positively correlated in the rainy season, but in the dry season the relationship tended to be reverse. This behaviour of 210Po in the coastal region was explained by the variation of pH of seawater and by the complexation of the isotope with DOC. The Kd(s) found in this study was in an order lower compared to that reported by Malaysian researchers for the Thailand Gulf. The most important source of 210Po was suggested to be from in-situ generation by the decay of its grand-parent 210Pb which mainly derived from the atmospheric fall-out.